2005
DOI: 10.1016/j.ydbio.2005.03.025
|View full text |Cite
|
Sign up to set email alerts
|

The nanos translational control element represses translation in somatic cells by a Bearded box-like motif

Abstract: Developmental control of translation is frequently mediated by regulatory elements that reside within 3' untranslated regions (3' UTRs). Two stem-loops within the nanos 3' UTR translational control element (TCE) act independently to direct translational repression of maternal nanos mRNA in the ovary or embryo. We have previously shown that the nanos TCE can also function in select somatic sites. Using an ectopic expression screen, we now identify a new site of TCE function, the dorsal pouch epithelium. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Double fluorescence in situ hybridization (FISH) using tyramide signal amplification was performed as described (Kosman et al, 2004). Immunofluorescence was performed as previously described (Duchow et al, 2005) using embryos heat-fixed in 68 mM NaCl/0.03% Triton X-100, with rabbit anti-Vas (1:10000; gift from R. Lehmann) and Alexa Fluor-568 goat anti-rabbit (1:1000; Molecular Probes). Embryos were mounted in 90% glycerol/100 mM Tris pH 8.0 and imaged with a Zeiss LSM510 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Double fluorescence in situ hybridization (FISH) using tyramide signal amplification was performed as described (Kosman et al, 2004). Immunofluorescence was performed as previously described (Duchow et al, 2005) using embryos heat-fixed in 68 mM NaCl/0.03% Triton X-100, with rabbit anti-Vas (1:10000; gift from R. Lehmann) and Alexa Fluor-568 goat anti-rabbit (1:1000; Molecular Probes). Embryos were mounted in 90% glycerol/100 mM Tris pH 8.0 and imaged with a Zeiss LSM510 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…We expect that excess Nanos2 protein may negatively affect its own translational efficiency, but we have shown that the Nanos2-3Ј-UTR might be required for efficient translation also (Tsuda et al, 2006). Because the 3ЈUTR elements within the Nanos family of mRNAs have also been shown to be regulated by several proteins (Dahanukar and Wharton, 1996;de Moor et al, 2005;Duchow et al, 2005;Nelson et al, 2004), these factors may also affect the translational efficiency of Nanos2 in combination with other mechanisms.…”
Section: Research Articlementioning
confidence: 97%
“…Immunostaining of ovaries was performed as previously described (Shcherbata et al, 2004). Embryo immunostaining was performed as described (Duchow et al, 2005), except that for anti-Rump immunofluorescence, dechorionated embryos were heat-fixed in 68 mM NaCl/0.03% Triton X-100, transferred to PBS, and the vitelline membranes were manually removed using a 30-gauge needle. The following antibodies and dyes were used: 1:100 anti-Rump 10C3 (immunofluorescence), 1:100 anti-Rump 5G4 (immunohistochemistry), 1:10,000 rabbit anti-Vas (gift of R. Lehmann, Skirball Institute, New York), 1:1000 Alexa Fluor 568 goat anti-mouse (Invitrogen/Molecular Probes), 1:1000 Alexa Fluor 488 goat anti-rabbit (Invitrogen/Molecular Probes), 1:1000 Oregon Green 488 phalloidin (Invitrogen/Molecular Probes), 1:1000 Hoechst (ovaries), 1:1000 DAPI (embryos).…”
Section: Embryonic Cuticle Preparation In Situ Hybridization and Immmentioning
confidence: 99%